Allergy Frontiers: Therapy and Prevention - Pawankar, Ruby.; Holgate, Stephen T.; Rosenwasser, Lanny J. (Allergy Frontiers, 2010)
The prevalence of asthma and other allergic diseases is on the rise worldwide, with a marked impact on quality of life and socioeconomics. Allergy Frontiers comprises six volumes, each dedicated to a specific aspect of the disease to reflect the multidisciplinary character of the field and its explosive growth. Included are reviews by world-renowned scientists from Europe, North and South America, Australia, Japan, other parts of Asia, and South Africa. The fifth volume is dedicated to therapy and prevention of allergies, including pharmacotherapy and allergen-specific immunotherapy, with novel aspects and special considerations for particular groups such as children, the elderly, and pregnant women. This book serves as a valuable tool for scientists and as a practical guide for clinicians working in the fields of allergy, asthma, and immunology.